AA amyloidosis – Benefits and prospects of IL-6 inhibitors. Issue 2 (4th March 2019) - Okuda, Yasuaki
Abstract: AA amyloidosis may develop in patients with active chronic inflammation. Serum amyloid A (SAA), the precursor of the AA protein, is strongly amplified in the liver under the stimulation of inflammation-associated cytokines, such as IL-6, TNF, and IL-1. Sustained inflammation, aging, and polymorphisms in the SAA1.3 genotype are dependent risk factors for the formation of AA amyloidosis. The most rational treatment strategy for AA amyloidosis is to inhibit the production of SAA. Treatments for AA amyloidosis involving biologics have recently been emphasized. TNF inhibitors and abatacept reduce SAA levels; however, complete normalization is not always achieved. IL-6 inhibitors may normalize SAA levels in most patients in whom a sufficient concentration of medication is maintained in the blood. Therefore, treatments with IL-6 inhibitors represent an excellent therapeutic strategy for AA amyloidosis and have been verified by recent studies.